Strategies to increase mastery of science process skills in Section B UPSR's Science paper: a case study of Year 6 pupils in Sekolah Kebangsaan Matang Jaya, Padawan, Sarawak / Zurinawati Sekawi - Sekawi, Zurinawati (2016)
This study was carried out to finding the strategies to increase mastery of science process skills in Section B of UPSR’s Science paper, at Sekolah Kebangsaan Matang Jaya, Padawan, Sarawak. The respondents for this study were 20 moderate achievers from Year Sik pupils and also 5 Science teachers. The researcher used the quantitative research method, through questionnaires and open-ended questions to collect data. The questionnaires that were used to collect the data that were divided into two categories: pupils and teachers. Each questionnaires has two sections: Section 1 and Section 2. The data collected in Section 1 was on the respondents’ demographic profile while the data in Section 2 was to gather understanding of science process skill by the pupils and the teacher’s problems in teaching Science subject and their suggestion to improve pupils’ science process skill. The 20 pupils were asked to sit for a similar science Section B test paper, to get both pre-test and post-test results. The result of this study shows that the science process skills improved pupils perform in the science papers. It can be concluded that the strategies introduced by the teachers had help the pupils to mastery the questions in Section B of UPSR’s science paper.